Podoconiosis in East and West Gojam Zones, Northern Ethiopia - Molla, Yordanos B. (Public Library of Science, 2012)
BACKGROUND: Podoconiosis is a neglected tropical disease (NTD) that is prevalent in red clay soil-covered highlands of tropical Africa, Central and South America, and northern India. It is estimated that up to one million cases exist in Ethiopia. This study aimed to estimate the prevalence of podoconiosis in East and West Gojam Zones of Amhara Region in northern Ethiopia. METHODOLOGY/PRINCIPAL FINDINGS: A cross-sectional household survey was conducted in Debre Eliyas and Dembecha woredas (districts) in East and West Gojam Zones, respectively. The survey covered all 17,553 households in 20 kebeles (administrative subunits) randomly selected from the two woredas. A detailed structured interview was conducted on 1,704 cases of podoconiosis identified in the survey. RESULTS: The prevalence of podoconiosis in the population aged 15 years and above was found to be 3.3% (95% CI, 3.2% to 3.6%). 87% of cases were in the economically active age group (15–64 years). On average, patients sought treatment five years after the start of the leg swelling. Most subjects had second (42.7%) or third (36.1%) clinical stage disease, 97.9% had mossy lesions, and 53% had open wounds. On average, patients had five episodes of acute adenolymphangitis (ALA) per year and spent a total of 90 days per year with ALA. The median age of first use of shoes and socks were 22 and 23 years, respectively. More men than women owned more than one pair of shoes (61.1% vs. 50.5%; χ(2) = 11.6 p = 0.001). At the time of interview, 23.6% of the respondents were barefoot, of whom about two-thirds were women. CONCLUSIONS: This study showed high prevalence of podoconiosis and associated morbidities such as ALA, mossy lesions and open wounds in northern Ethiopia. Predominance of cases at early clinical stage of podoconiosis indicates the potential for reversing the swelling and calls for disease prevention interventions.